On the Existence of a Noninner Automorphism of Order $p$ for $p$-Groups - Bondarchuk, L. Yu.; Pylyavs'ka, O. S. (Ukrains’kyi Matematychnyi Zhurnal, 2001)
We obtain sufficient conditions for the existence of a noninner automorphism of order p for finite p-groups. We show that groups of order p n (n < 7, p is a prime number, p > 3) possess a noninner automorphism of order p.